2022
DOI: 10.1021/accountsmr.1c00270
|View full text |Cite
|
Sign up to set email alerts
|

The Renaissance of Functional Hybrid Transition-Metal Halides

Abstract: Metrics & More Article RecommendationsCONSPECTUS: There is an extensive history of research on both inorganic and hybrid metal halides, with the latter being first reported in the 1960s. Although work on hybrid systems has progressed steadily over the last 60 years, it has enjoyed a major renaissance during the last 5 years. This has arisen as a consequence of the 2009 discovery of the outstanding optoelectronic properties of hybrid lead halides, such as (MA)PbI 3 (MA = methylammonium), and the recognition tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 60 publications
0
38
0
Order By: Relevance
“…Hybrid organic–inorganic metal halides show great potentials for a variety of optoelectronic applications such as solar cells [1, 2] and light‐emitting diodes [3–5] . They are highly flexible with organic counterparts, [6] inorganic metals, [7] and halide components [8] . For example, hybrid lead halide perovskite materials have demonstrated highly diverse structural, optical, and electronic properties with the templating effects of organic cations and halide variations [9–11] .…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid organic–inorganic metal halides show great potentials for a variety of optoelectronic applications such as solar cells [1, 2] and light‐emitting diodes [3–5] . They are highly flexible with organic counterparts, [6] inorganic metals, [7] and halide components [8] . For example, hybrid lead halide perovskite materials have demonstrated highly diverse structural, optical, and electronic properties with the templating effects of organic cations and halide variations [9–11] .…”
Section: Introductionmentioning
confidence: 99%
“…Advanced multifunctional materials that integrate multiple properties in a single crystalline material have attracted a tremendous amount of research interest. In recent years, hybrid organic–inorganic metal halides have been considered promising functional materials because of their structural diversity and extraordinary photophysical properties. Due to the tunable compositions and flexible crystal structures of hybrid organic–inorganic metal halides, chiral moieties can be rationally introduced into the system as ligands or templating cations, enabling the construction of multifunctional materials. Chirality transfer from organic modules to inorganic moieties can be effectively realized not only through the formation of chemical bonds but also through spatial interactions. , Intrinsic chirality introduced in metal hybrid materials will generally break the symmetry, leading to novel chirality-related optoelectronic properties, such as circular dichroism (CD), , circularly polarized luminescence (CPL), second harmonic generation (SHG), pyroelectricity, piezoelectricity, and ferroelectricity . In addition, due to the interaction between chirality and spin, the introduction of chirality into organic–inorganic hybrid metal halides with a strong spin orbit coupling system (Pb and I) also has broad application prospects in spintronics. , …”
Section: Introductionmentioning
confidence: 99%
“…8 Along with the intriguing optical properties, Mn-based 0D hybrid materials are an important class of light-emitting materials that can replace toxic lead-based halide perovskites. [35][36][37][38][39][40][41][42][43][44][45][46] Recent reports have proven the possibility of fabricating lightemitting devices with Mn(II) complexes. Chen et al 47 reported solution-processed green LEDs using an ionic tetrabromide Mn(II) complex and reported an EQE of 9.6% and a brightness of 2339 cd m À2 , whereas Huang et al 48 fabricated vacuum processed LEDs using neutral tetrahedral Mn(II) complexes and reported a high current efficiency (CE) and power efficiency (PE) of 35.47 cd A À1 and 34.35 lm W À1 and with a maximum luminescence of 1412 cd m À2 .…”
Section: Introductionmentioning
confidence: 99%